SOCIAL MEDIA, CIVIC ENGAGEMENT, AND THE SLACKTIVISM HYPOTHESIS: LESSONS FROM MEXICO'S "EL BRONCO". - Howard, Philip N.; Savage, Saiph; Saviaga, Claudia Flores; Toxtli, Carlos; Monroy-Hemández, Andrés (Journal of International Affairs)
Does social media use have a positive or negative impact on civic engagement? The cynical “slacktivism hypothesis” holds that if citizens use social media for political conversation, those conversations will be fleeting and vapid. Most attempts to answer this question involve public opinion data from the United States, so we offer an examination o f an important case from Mexico, where an independent candidate used social media to communicate with the public and eschewed traditional media outlets. He won the race for state governor, defeating candidates from traditional parties and triggering sustained public engagement well beyond election day. In our investigation, we analyze over 750,000posts, comments, and replies over three years o f conversations on the public Facebook page o f “El Bronco. ” We analyze how rhythms o f political communication between the candidate and users evolved over time and demonstrate that social media can be used to sustain a large quantity o f civic exchanges about public life well beyond a particular political event.